Dampak Pandemi Covid-19 terhadap Perilaku Belajar, Sosial dan Kesehatan bagi Mahasiswa FKIP Universitas Palangka Raya - Ulfa, Zuly Daima; Mikdar, Ujen Zenal (JOSSAE (Journal of Sport Science and Education), 2020)
The covid-19 pandemic forced restrictions on social, economic, religious activities including college activities. The closure of several public facilities, sports arenas, shops and lectures conducted online has an impact on Palangka Raya University (UPR) students. The study aims to analyze the changes in learning, social and health of UPR students. This study was quantitative research and used cross-sectional design. Samples were FKIP UPR students that were selected by simple random sampling. Data were collected using online questionnaire. The impact of the covid-19 pandemi for students in college activities is the adjustment of online methode, because some areas are constrained by internet signal. Social communication is increasing in cyberspace, as a result of cant meet directly. Students become more concerned about health behavior, which is mostly applied is washing hands. Covid-19 pandemic has an impact on learning behavior, social and health, but from the constraints experienced, students become more adaptive to identify technologies that can support learning, increasing social relations and application of healthy lifestyles. The conclusion is pandemic has a negative impact on learning which is related to unstable signal, but there is also positive impact, which is improving skills related to using technology, social communication and health behavior.